Determinant of Entrepreneurial Interest of College Students from Non-Entrepreneurial Families in Banten Province, Indonesia - Yohana F. Cahya Palupi Meilani; Leonardo M. Canoy, Jr; Elvitriana Intan Novita (Universitas Pelita Harapan, 2024)
The purpose of this study was to see the effect of entrepreneurship education, creativity, entrepreneurial mindset, self-efficacy on entrepreneurial interest in Banten, Indonesian students. The reason is that the majority of students in Indonesia, including in Banten Province who come from non-entrepreneurial families, prefer to look for work after graduating rather than starting their own business. Quantitative research method with probability sampling with purposive sampling, namely active students who received entrepreneurship education from non entrepreneurial families as many as 272 respondents. Data processing using PLSSEM with software 4.0. The results of the study showed that entrepreneurship education, creativity, entrepreneurial mindset and self-efficacy had a significant effect on entrepreneurial interest in students. Self-efficacy was able to moderate the relationship between entrepreneurship education. Creativity and entrepreneurial mindset on entrepreneurial interest in students. Contributions for students from non-entrepreneurial families are expected to provide information on the relationship between entrepreneurship education, creativity, entrepreneurial mindset and self efficacy which are important factors that can foster entrepreneurial interest